Impact of the COVID-19 Pandemic on Forensic Medicine Residency Training - Yıldırım, Mahmut Şerif; Aydogan, Halit Canberk; Zengin, Hatice Yagmur; Akcan, Ramazan; Tumer, Ali Riza (The Bulletin of Legal Medicine, 2022)
Objective: This paper aims to assess the impact of SARS-CoV2 outbreak on forensic medicine residency training and to reveal implemented methods to keep the standard of residency education to prevent pandemic’s catastrophic effects on education of forensic medicine residents in Turkey. Methods: Two online-based surveys were prepared towards “Residents of forensic medicine” and “Head of departments”. Survey-1 completed by 125 forensic medicine residents and Survey-2 completed by 18 heads of forensic medicine departments from different regions of Turkey. Results: More than half of the residents who started their clinical training practice before outbreak of pandemic reported that there has been a decrease in numbers of clinical practical activities, and half of the residents stated that lectures/meetings have been suspended due to the pandemic. Distance learning/meeting applications in educational activities were found "partially useful" or "useful" by 83.2% of the residents (n=104). Residents who pointed out a change in practical autopsy training reported that this change has negatively affected their forensic medicine residency training. Conclusions: Sharing our results might force potential implementations to prevent worsening and improve forensic medicine residency training here and worldwide to identify effective responses to such unexpected issues.